Biodiversity conservation, food security, and carbon storage potential of local agroforestry practices in the Bird’s Head Region of Papua, Indonesia - HENDRI HENDRI; JULIUS DWI NUGROHO; ADITYA RAHMADANIARTI; NURLAELA NURLAELA; SARASWATI PRABAWARDANI; FIONA DJUNITA NATALIA LUHULIMA; CHRISTOPHER GARDINER; FRANCINE HEMATANG (Society for Indonesian Biodiversity, 2024)
Abstract. Hendri, Nugroho JD, Rahmadaniarti A, Nurlaela, Prabawardani S, Luhulima FDN, Gardiner C, Hematang F. 2024. Biodiversity conservation, food security, and carbon storage potential of local agroforestry practices in the Bird’s Head Region of Papua, Indonesia. Biodiversitas 25: 4315-4332. Local Agroforestry Practices (LAPs) in the Papua Region, Indonesia, which are still under-researched, play a crucial role in biodiversity conservation through sustainable crop rotation systems, intensification, and technological adaptability. This research aims to develop an improved intensification model that integrates these LAPs with sustainable agroforestry practices, biodiversity conservation, food security measures, and adaptive responses to climate change and extreme conditions. The study utilized the Focus Group Discussion (FGD) method, demonstration plot, Participatory Rural Appraisal (PRA) type selection of LAPs, and economic and allometric equations. The findings revealed a meticulous species selection process that considered biodiversity, resulting in 24 species classified as Least Concern (LC), 2 species classified as Near Threatened (NT), 1 species classified as Vulnerable (VU), and 2 species classified as Endangered (EN). The LAPs implementation achieved a Food Security (FS) score of 45,23% and 38.47% for Only Used (OU). Importantly, the total revenue generated by the LAPs design in Moswaren, Aimas, and Manokwari Village is nearly the same, with an average of Rp 16,327,231.00, Rp 16,640,731.00 and Rp 15,848,675.00 per year, respectively. This represents a significant economic impact, with the increase being 2.93-5.04 times greater than typical LAPs; this significant contribution to biodiversity conservation is a testament to their value. The aggregate carbon content across the three sites varied between 223.80 and 279.05 tC/ha.